New multiple labelling method for improved satellite cell identification in human muscle: application to a cohort of power-lifters and sedentary men - Lindström, Mona; Thornell, Lars-Eric (Histochemistry and cell biology, 2009)
Presently applied methods to identify and quantify human satellite cells (SCs) give discrepant results. We introduce a new immunofluorescence method that simultaneously monitors two SC markers (NCAM and Pax7), the basal lamina and nuclei. Biopsies from power-lifters, power-lifters using anabolic substances and untrained subjects were re-examined. Significantly different results from those with staining for NCAM and nuclei were observed. There were three subtypes of SCs; NCAM⁺/Pax7⁺ (94%), NCAM⁺/Pax7⁻ (4%) and NCAM⁻/Pax7⁺ (1%) but large individual variability existed. The proportion of SCs per nuclei within the basal lamina of myofibres (SC/N) was similar for all groups reflecting a balance between the number of SCs and myonuclei to maintain homeostasis. We emphasise that it is important to quantify both SC/N and the number of SCs per fibre. Our multiple marker method is more reliable for SC identification and quantification and can be used to evaluate other markers of muscle progenitor cells.